Lower prevalence of chronic itch in haemodialysis patients on loop diuretics: results from GEHIS (German Epidemiological Hemodialysis Itch Study) - Hayani, Kinan; Kunzmann, Kevin; Weiß, Melanie; Weisshaar, Elke (Journal of the European Academy of Dermatology and Venereology, 2017)
Background Chronic itch (CI) is a very tormenting symptom in haemodialysis (HD) patients. GEHIS (German Epidemiological Hemodialysis Itch Study) is a representative cross-sectional study showing that current chronic itch (CI) affects 25.2% of haemodialysis (HD) patients. Objective We investigated drug intake and possible associations between CI and medications of HD patients. Methods Eight hundred and sixty HD patients from a randomly selected cluster sample of 25 dialysis units (GEHIS) in Germany were investigated. Statistical analyses were performed using R (version 3.3.0) for Windows. Logistic regression was used to identify influential covariates for prevalence of chronic itch and intensity of itch. Results Taking loop diuretics (furosemide, torasemide) was significantly negatively associated with the occurrence of CI in HD patients meaning that those who had received any type of loop diuretics were significantly less likely to suffer from less CI compared to those who had not taken them. There were no associations of CI with other medications. No correlation was detected between the intensity of itch and the intake of loop diuretics or any other medication. Conclusion Loop diuretics may have an impact on the development of CI in HD patients. As it is most likely that a multifactorial origin may explain CI in HD, future research should also focus on the role of loop diuretics in CI, both on a clinical as well as on a molecular level.
Gesehen am 18.10.2018